2012
DOI: 10.1088/0953-8984/24/23/233203
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional phonon transport in graphene

Abstract: Properties of phonons -quanta of the crystal lattice vibrations -in graphene have attracted strong attention of the physics and engineering communities. Acoustic phonons are the main heat carriers in graphene near room temperature while optical phonons are used for counting the number of atomic planes in Raman experiments with few-layer graphene. It was shown both theoretically and experimentally that transport properties of phonons, i.e. energy dispersion and scattering rates, are substantially different in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
412
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(441 citation statements)
references
References 145 publications
(516 reference statements)
24
412
0
5
Order By: Relevance
“…Recent studies 9,23,[48][49][50] showed that the thermal conductivity of graphene increases logarithmically (~logL) with the size of sample, which is taken to fit MD results shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies 9,23,[48][49][50] showed that the thermal conductivity of graphene increases logarithmically (~logL) with the size of sample, which is taken to fit MD results shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The successful exfoliation of graphene [1] and discoveries of its unique electrical [2,3] and thermal [4][5][6][7] properties have motivated searches for other quasi two-dimensional materials with interesting properties, as well as techniques for their synthesis and characterization [8][9][10][11][12]. As a group, layered van der Waals materials [8] can be cleaved mechanically or exfoliated chemically by breaking the relatively weak bonding between the layers.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical investigations employed different models of the lattice vibrations, molecular dynamics simulations, density functional method and Boltzmann transport equation approach [13][14][19][20][21][22][23]. Recently the attention has been shifted to twisted few-layer graphene (T-FLG), which demonstrates intriguing electron [24][25][26][27] and phonon properties [28][29][30][31][32][33][34][35][36].…”
mentioning
confidence: 99%
“…Here  is the phonon frequency, [19,32,39]. Therefore, a proper choice of the force constant matrices  is crucial for obtaining the correct phonon frequencies and for accurate calculation of phonon specific heat.…”
mentioning
confidence: 99%